Expectativas de la familia indígena frente a la educaciónanálisis de caso en la comunidad San José, parroquia Tabacundo. - Paguay Yupa, Janneth Patricia (2017)
For parents, education today is the main axis because through it they seek to improve the quality of life of families that their children have a future different from that of their parents, for that reason, the decision to opt for a Bilingual Intercultural Education or a Hispanic education is of vital importance. In brief, the analysis of the history of Bilingual Intercultural Education from the colony, the scope achieved with the work and participation of Dolores Cacuango and its contribution to personal and collective development in the indigenous sector. In the past, indigenous families could not access education for different reasons such as lack of economic resources, domestic work, little knowledge of spanish, lack of access to education and lack of interest on the part of their parents of access to education. Precisely, today with the technological boom and the new forms of life the access to one type of education or another is indispensable for a better future. In order to know the expectations of the indigenous families, the interviews and the collected information are carried out, through a detailed analysis of each given answer, the parents' disagreement with the education they receive in their sector is identified. Interest in opting for an education in the urban sector.